Development of an app for Android phones - Poh, Jonathan Shengliang (2018)
Technology today is advancing exponentially. Technology has brought advancements in agriculture, education, transportation and communication, among others. These technological advancements are made possible by professionals and this includes engineers. Therefore, engineers are more in demand than ever. However, there has been a decline in engineer population in recent years and it is a national issue. One of the factors that cause this decline is the lack of coverage of engineering topics in primary and secondary schools. To provide students with a medium to learn and get exposed to engineering topics, electrical and electronics engineering in particular, an edutainment android application is being developed. This edutainment application uses Augmented Reality (AR) technology to create an interactive and intuitive learning medium for students. AR is gaining popularity in the educational industry because it is visually appealing and it allows students to interact with virtual objects and real world objects. Therefore, it will increase students’ interest in electrical and electronic engineering. This report focuses on the early phase of an application development which includes market research, gathering feedbacks, designing and developing the concept of an AR based edutainment application. Further developments and trail on students are required to develop the application an optimal learning platform for students. This report will also provide directions and guidance for future developers who might develop similar application concept.